Photobiomodulation and Coenzyme Q10 Treatments Attenuate Cognitive Impairment Associated With Model of Transient Global Brain Ischemia in Artificially Aged Mice - Salehpour, Farzad; Farajdokht, Fereshteh; Mahmoudi, Javad; Erfani, Marjan; Farhoudi, Mehdi; Karimi, Pouran; Rasta, Seyed Hossein; Sadigh-Eteghad, Saeed; Hamblin, Michael R.; Gjedde, Albert (Frontiers in Cellular Neuroscience, 2019)
Disturbances in mitochondrial biogenesis and bioenergetics, combined with neuroinflammation, play cardinal roles in the cognitive impairment during aging that is further exacerbated by transient cerebral ischemia. Both near-infrared (NIR) photobiomodulation (PBM) and Coenzyme Q10 (CoQ10), administration are known to stimulate mitochondrial electron transport that potentially may reverse the effects of cerebral ischemia in aged animals. We tested the hypothesis that the effects of PBM and CoQ10, separately or in combination improve cognition in a mouse model of transient cerebral ischemia superimposed on a model of aging. We modeled aging by 6-week administration of D-galactose (500 mg/kg/subcutaneous) to mice. We subsequently, induced transient cerebral ischemia by bilateral occlusion of the common carotid artery (BCCAO). We treated the mice with PBM (810 nm transcranial laser) or CoQ10 (500 mg/kg; by gavage), or both, for two weeks after surgery. We assessed cognitive function by the Barnes and Lashley III mazes and the What-Where-Which (WWWhich) task. PBM or CoQ10, or both, improved spatial and episodic memory in the mice. Separately and together, the treatments lowered reactive oxygen species, and raised ATP and general mitochondrial activity, as well as biomarkers of mitochondrial biogenesis, including SIRT1, PGC-1α, NRF1, and TFAM. Neuroinflammatory responsiveness declined, as indicated by decreased iNOS, TNF-α, and IL-1β levels with the PBM and CoQ10 treatments. Collectively, the findings of this preclinical study imply that the procognitive effects of NIR PBM and CoQ10 treatments, separately or in combination, are beneficial in a model of transient global brain ischemia superimposed on a model of aging in mice.